Hepatic Lamp2a deficiency promotes inflammation of murine autoimmune cholangitis via affecting bile acid metabolism - Qingling Fan; Guanya Guo; Yinan Hu; Yi Lu; Rui Su; Jiaqi Yang; Erzhuo Xia; Shuoyi Ma; Miao Zhang; Jingbo Wang; Ting Li; Ying Han (iScience)
Summary: Primary biliary cholangitis is characterized by breaking of immune tolerance and disorders of bile acid metabolism. Our previous study found that abnormal expression of Lamp2 was detected in PBC patients. However, the specific role of Lamp2a in disease progression is still unclear. In this study, we showed that hepatic-specific Lamp2a deficiency could aggravate the inflammatory phenotype of murine autoimmune cholangitis. Mechanistically, the loss of Lamp2a in hepatocytes contributed to the abnormal accumulation of Acot8, thus altered the bile acid components, thereby enhancing the lymphocyte activities, and ultimately promoting the inflammatory phenotype of model mice. Moreover, we also found that Acot8 knockdown could alleviate the liver inflammation caused by Lamp2a deficiency. Altogether, our findings explored the effect of Lamp2a deficiency on the murine autoimmune cholangitis by the perspective of bile acid metabolism, and marked the possibility of Acot8 as a new target for the treatment of PBC disease.